EFEKTIFITAS YOGA PRANAYAMA DAN AROMATERAPI TERHADAP PENINGKATAN KUALITAS TIDUR DAN KUALITAS HIDUP PASIEN KANKER - Ni Nyoman Indah Purnamasari; Ni Luh Widani (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Cancer is cells that grow uncontrollably and include chronic diseases that cause physiological andpsychological problems. The purpose of this research were determine of an effectiveness of yogapranayama and aromatherapy to improve sleep quality and quality of life for cancer patients. Thetype of this study is an experimental with non equivalent control group pretest-posttest design, with126 samples with purposive sample. Pittsburgh Sleep Quality Index (PSQI) used to evaluated sleepquality and Quality of Life Questionnaire (QLQ C30) to evaluatde quality if life. The result of thisresearch using sample paired t-test there was a difference in sleep quality and quality of life beforeand after intervention yoga and aromatherapy (p 0.00;<0,05); by using one way ANOVA, therewas different between three group and different improvement between intervention and controlgroup (p<0,05 It?s concluded that yoga and aromatherapy effective improve sleep quality andquality of life to cancer patients and the more effective in aromatherapy. The cancer patients aresuggested to take yoga and aromatherapy as a complementary therapy to improve sleep quality andquality of life.